Role of HNF6 in liver homeostasis and pathophysiology - Miaomiao Tian; Weizhen Gao; Shujun Ma; Huiling Cao; Yu Zhang; Fuxiang An; Jianni Qi; Zhen Yang (Molecular Medicine, 2025)
Abstract Background Hepatocyte nuclear factor 6 (HNF6), a member of the HNF family, contains single cleft and homologous domains, which form a DNA-binding region that targets the promoter regions of genes that bind to liver-specific genes and regulate their expression. Furthermore, HNF6 is highly expressed as an HNF in the liver. Main body HNF6 regulates not only the formation of the liver but also the proliferation and differentiation of hepatocytes. Additionally, HNF6 controls the migration and adhesion of hepatocellular carcinoma cells and plays a significant role in liver metabolism. Its expression is affected by epigenetic modifications such as DNA methylation, post-translational modifications, and microRNAs. Recently, HNF6 was also found to be expressed in tissues, such as the pancreas, intestine, and lungs, where it controls their formation by regulating cell differentiation and influences their pathophysiological processes via various mechanisms. Conclusion In this review, we highlight advances in HNF6-related research concerning liver diseases and provide a summary of its potential mechanisms of action as a transcription factor in regulating downstream genes and epigenetic modifications. We also highlight gaps in liver disease research and provide future research directions for the application of HNF6 and its downstream molecules as attractive targets in the treatment of liver diseases.